1981
DOI: 10.1159/000182203
|View full text |Cite
|
Sign up to set email alerts
|

Protein Losses in Continuous Ambulatory Peritoneal Dialysis

Abstract: Protein losses in peritoneal dialysate were determined in 220 exchanges from 19 patients undergoing continuous ambulatory peritoneal dialysis. With four exchanges per day, mean protein losses in 79 dialysate collections over 24 h were 12.2 g. Protein losses per exchange increased with cycle time, however, protein losses per day were greater with more exchanges per day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 6 publications
2
15
0
Order By: Relevance
“…Plasma IgG levels were measured in 65 patients, and IgG clearance was calculated as follows: D/P X V /1,440, where D » dialysate IgG concentration, P = plasma IgG concentration, V = dial ysate volume, 1,440 = minutes in 24 h. Plasma proteins were mea sured by the biuret method and albumin by the bromocresol green method. IgG was measured in the 24-hour dialysate and in plasma by commercially available nephelometric methods [8,9] in the hospital laboratory or at commercial laboratories.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma IgG levels were measured in 65 patients, and IgG clearance was calculated as follows: D/P X V /1,440, where D » dialysate IgG concentration, P = plasma IgG concentration, V = dial ysate volume, 1,440 = minutes in 24 h. Plasma proteins were mea sured by the biuret method and albumin by the bromocresol green method. IgG was measured in the 24-hour dialysate and in plasma by commercially available nephelometric methods [8,9] in the hospital laboratory or at commercial laboratories.…”
Section: Methodsmentioning
confidence: 99%
“…Considerable amounts of protein are removed from the body during peritoneal dialysis (PD), roughly between 5 and 15 g/day during continuous ambulatory PD [1], with albumin representing >90% of the peritoneal protein determined [2]. Several factors can affect the quantity of peritoneal protein loss (PPL), for example, the frequency and duration of the dialysis, the composition of the fluid infused and peritoneal infections [1, 3].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors can affect the quantity of peritoneal protein loss (PPL), for example, the frequency and duration of the dialysis, the composition of the fluid infused and peritoneal infections [1, 3]. In recent studies, PPL has been shown to be associated with the prevalence of peripheral arterial disease (PAD), cardiovascular events and higher mortality in PD patients [4-6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition. CAPD treatment leads to both an increased loss of amino acids and proteins into the dialvsatc [9][10][11][12] and decreased appetite, probably due to peri toneal glucose absorption and abdominal distension by the dialysis solution. Even though most patients maintain normal serum total protein levels and albumin homeosta sis during the initial months on CAPD [13][14][15], long-term CAPD treatment results in decreased total body nitrogen and a reduced protein intake < 1 g/kg body weight/day [13.…”
Section: Introductionmentioning
confidence: 99%